Morfem Terikat Pada Buku Cerita Rakyat Nusantara 34 Provinsi - Reni Rokhayati; Ila Nafilah; Yulia Aguatin (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to find and describe bound morphemes contained Indonesian Folklore from 34 Provinces. This research uses Morphological theory. This research uses a qualitative descriptive method with Content Analysis techniques. The results of this research are: (1) There are 233 prefixes in Folklore of the Archipelago from 34 Provinces consisting of 6 prefixes (2.6%), 10 prefixes (4.3%), prefixes in- as many as 20 findings (8.6%), Prefix Men- as many as 44 findings (18.9%), Prefix me- as many as 48 findings (20.6%), Prefix me0n- as many as 60 findings (25.7%), prefix mem- as many as 40 findings (17.1%), prefix se- many as 5 findings (2.1%). There are 200 suffixes in Indonesian Folklore, the suffix -an totaling 50 findings (25%), the suffix -kan 100 findings (50%), and the suffix -nya 50 findings (25%).